Perancangan User Interface (UI) Sistem Social Media Scheduler dengan Metode Rapid Application Development (RAD) - Luther Aldo Christian; Siska Narulita (Pixel :Jurnal Ilmiah Komputer Grafis, 2024)
Scheduling content on social media effectively and efficiently has become an important need for users, especially users who use social media as a tool to help run their business or organization. This research aims to design a user interface for a website-based social media scheduling application using the Rapid Application Development method and Unified Modeling Language (UML). This method was chosen because development can be done quickly through literacy that involves users so that it can fulfill everything needed to create an optimal system. The research stage begins with user interviews, and later this data will be used to develop an initial UI design prototype designed using Figma. UML is used to visualize the design model and also how the system will run later. This system is expected to help make posting social media content easier.